Catalytic transesterification of Pistacia chinensis seed oil using HPW immobilized on magnetic composite graphene oxide/cellulose microspheres - Li, Tian-Feng; Wang, Xi-Qing; Jiao, Jiao; Liu, Ju-Zhao; Zhang, Hua-Xia; Niu, Li-Li; Zhao, Chun-Jian; Gu, Cheng-Bo; Efferth, Thomas; Fu, Yu-Jie (Renewable energy, 2018)
In the present study, magnetic composite graphene oxide/cellulose (GO/CM@Fe3O4) microspheres were prepared as support material, which are cost-efficient, non-toxic and environmental friendly. The microspheres with higher adsorption capacity were further modified using triethylene tetramine (TETA), and H3PW12O40 (HPW) was immobilized to form GO/CM-NH2@Fe3O4-HPW microspheres as heterogeneous catalyst for biodiesel production. The novel heterogeneous catalyst was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), Brunauer-Emmett-Teller (BET) and X-ray diffractometry (XRD). For the first time, GO/CM-NH2@Fe3O4--HPW was applied in the transesterification of highly-acidic Pistacia chinensis seed oil to biodiesel. Under optimal reaction conditions 80 °C, methanol/oil molar ratio 12:1, catalyst 15 wt% (w/w of oil) for 8 h, a 94% biodiesel yield was achieved. The heterogeneous catalyst could be easily separated from the reaction system by using magnetic field and efficiently recycled for at least six times. This novel procedure overcomes the disadvantages of the current catalyst support such as active site leaching, complicated preparation process and high costs. Therefore, it was a potential novel heterogeneous catalyst for biodiesel production. [Display omitted] •GO/CM-NH2@Fe3O4 was prepared as a support material to immobilize HPW.•The novel support was employed to immobilize HPW for biodiesel production.•Catalytic transesterification of Pistacia chinensis seed oil using GO/CM-NH2@Fe3O4-HPW was investigated.